Professionelles Schreiben in mehreren Sprachen: Strategien, Routinen und Sprachen im Schreibprozess - Dengscherz, Sabine (2019)
How do professional writers adapt their strategies, routines and use of language resources to different writing situations? 17 case studies explore patterns and interrelations in writing processes of multilingual writers: 13 students and 4 researchers have recorded their writing processes with screen-capturing software and additionally, provided information about their language- and writing biographies. Based on the cross case analysis of these 17 case studies, the PROSIMS writing process model conceptualizes influence factors and dynamic interrelations in writing processes.